Reorientation of the Purpose of Punishment in the National Criminal Code: A Humanistic Approach in Indonesian Criminal Law - Sumartini Dewi; Sri Setiawati (Dinasti Research, 2026)
The reform of criminal law in Indonesia through Law Number 1 of 2023 concerning the National Criminal Code represents a significant transformation in the orientation of the national sentencing system. Historically, Indonesia’s criminal justice framework has largely been influenced by a retributive paradigm, where punishment is primarily viewed as retaliation for criminal acts committed by offenders. However, the development of modern criminal law thought has encouraged the adoption of a more comprehensive approach that emphasizes humanitarian values. In this context, the National Criminal Code introduces a new paradigm that incorporates humanistic and restorative principles, while emphasizing social recovery. This approach does not merely focus on imposing sanctions on offenders, but also seeks to repair the social relationships disrupted by crime, ensure adequate protection for victims, and support the rehabilitation and social reintegration of offenders. This study aims to examine the reorientation of sentencing objectives under the National Criminal Code and to analyze how a humanistic approach is integrated into Indonesia’s criminal law framework. The research employs a normative juridical method, utilizing statutory and conceptual approaches. The analysis is conducted through an examination of the provisions contained in the National Criminal Code as well as relevant criminal law literature. The findings indicate that the National Criminal Code establishes a new direction for the Indonesian sentencing system by emphasizing a balance between public protection, victim restoration, and offender rehabilitation. Consequently, punishment is no longer solely perceived as a mechanism of retaliation, but rather as a legal instrument aimed at achieving substantive justice, maintaining social order, and promoting a more humane and equitable criminal justice system.